Manufacturing consumer consent via contest entry form as promotional genre - Soo, Jacquelyn Poh Yoke (2011)
The research interest of this thesis was to describe, interpret and explain the influence of a particular genre of promotional discourse on consumers. Those in the advertising industry loosely identify this genre as the contest entry form or CEF. Key questions include analysing the verbal and visual strategies employed in CEFs in relation to specific products that were promoted, how promotional advertisers use these linguistic and non-linguistic strategies to manufacture consumer consent, and if there were any differences in perceptions about CEFs between consumers at large and those whose professions are related to the promotional and/ or advertising fields. The study used the mixed methods approach based on Creswell’s (2003) sequential exploratory design to analyse data in two phases. In the qualitative phase, a textual corpus of 118 CEFs collected from major supermarkets throughout the Klang Valley, Malaysia was examined. Eight key verbal and three key visual components were identified. Embedded underlying strategies within the verbal components include foregrounding, backgrounding, presupposition and connotation while those found within visual components included composition, visual modality and using structures of representation. In the quantitative phase, survey data from two groups of respondents (60 from the promotions and advertising fields; 59 from those whose professions were not related to either field) were analysed. The results showed that while occupational insights did make a difference in certain areas such as those pertaining to questionable criteria like the lucky draw and biggest spender, the implicit processes of “naturalisation” and “inculcation” (Fairclough, 1989, p. 75) may help explain how overall responses showed that insiders may be as “disadvantaged” (Janks, 1997, p. 28) as outsiders in relation to the messages the former encode as producers of the genre. It was thus concluded that the promotional genre in question largely succeeded in reaffirming commercial contest entry as a social practice that is a part of the goods purchasing activity. The researcher hopes that the present research provides deeper insights into promotional advertising discourse. Some guidelines for consumers to make more informed purchasing decisions, as well as suggestions for further research are made at the end of the thesis.